Análise do módulo de cisalhamento associado a modelo de Jeffreys modificado - Silva, Thales Augusto Barbosa Pinto (2017)
Thixotropic materials have economically important industrial applications. Recently proposed constitutive models describing its behavior are formulated by means of a two coupled equations system: the constitutive equation (based on viscoelastic classic models) and the rate equation (in which the microstructural evolution is described). The shear modulus and the viscosity coefficient(s) are considered, in such a class of models, as functions of the structural parameter. The expressions used for such functions are defined by satisfying some asymptotic limits, in a way that the model is physically consistent. However, there is no agreement as to the form in which the expressions are formulated. It is aimed to determine the form of shear modulus function, from rheological tests data, using a modified Jeffreys model. The obtainment of an expression for the shear modulus function is defined as an inverse problem and therefore the theory and some strategies associated were discussed. It is used a multi-objective framework together with the Tikhonov regularization method and the L-curve parameter-choice criterion in order to get the solution for associated ill-posed problems. The algorithms formalized throughout the work were implemented through a MATLAB developed code. As results, a new proposal for the shear modulus function were obtained and the parameters associated with the model constituted of this new proposal are fitted to rheological tests data.